2015
DOI: 10.3749/canmin.1400100
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Gahnite In Granitic Pegmatites From the Pampean Pegmatite Province, Argentina: Implications For Pegmatite Fractionation

Abstract: Gahnite from LCT granitic pegmatites of the Comechingones (Blanca Dora, Juan Román, Magdalena, La Ona, and Sin Nombre pegmatites) and Conlara (Nancy pegmatite) pegmatite districts, Argentina, was analyzed to investigate the relationship between its chemistry, pegmatite mineralogy, and pegmatite melt evolution. Based on the molecular proportions of endmembers (gahnite, hercynite, spinel, and galaxite) the composition of gahnite in these pegmatites is defined by the ranges Ghn 77.7-91.0 Hc 7.4-20.0 Spl 0.25-3.37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…7), together with very low Mg and Mn contents, indicating that they formed from highly differentiated melts. These melts were, indeed, more evolved than the Pampean Range granitic pegmatites from central Argentina studied by Heimann et al (2015).…”
Section: Insights Into Petrogenesis Of Santa Elena and Tres Tetas Pegmatitesmentioning
confidence: 74%
See 3 more Smart Citations
“…7), together with very low Mg and Mn contents, indicating that they formed from highly differentiated melts. These melts were, indeed, more evolved than the Pampean Range granitic pegmatites from central Argentina studied by Heimann et al (2015).…”
Section: Insights Into Petrogenesis Of Santa Elena and Tres Tetas Pegmatitesmentioning
confidence: 74%
“…Gray field corresponds to Nb-Ta oxides from Totoral LCT rare-element pegmatite district, San Luis, Argentina (Galliski et al 2019). Gray arrow suggests the fractionation trend of Ta/(Ta + Nb) vs. Mn/(Mn + Fe) of columbite group minerals in El Quemado pegmatites Heimann et al (2015) concluded that the major element composition of gahnite in granitic pegmatites can effectively be used to determine the relative degree of evolution of pegmatite-forming melts. The composition of gahnite in the Santa Elena pegmatites is characterized by very high Zn content and Zn/Fe 2+ ratios (Fig.…”
Section: Insights Into Petrogenesis Of Santa Elena and Tres Tetas Pegmatitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Gahnite (ZnAl 2 O 4 ), the Zn end-member of the spinel group of minerals ([Zn,Fe,Mg]Al 2 O 4 ), occurs as an accessory mineral in granitic pegmatite dikes (e.g., Nêmec 1973;Batchelor and Kinnaird 1984;Spry and Scott 1986b;Morris et al 1997;Heimann et al 2015). In addition, gahnite is a common accessory mineral in metamorphosed massive sulfide deposits and Zn-rich hydrothermal alteration zones, a rare accessory phase in marbles, metabauxites, skarns, and aluminous granulites, and even rarer in banded iron formations (e.g., Spry and Scott 1986a, b;Heimann et al 2005Heimann et al , 2006.…”
Section: Introductionmentioning
confidence: 99%